(3QSGdI aj CUhd Gdabgs - (3YHO Gddg Hf eMeO GdNQGSGfjs
(3ChdgG (B:s
.. (3hZjQg YOG GdJNUjU hHJbOe GdGTJQGc Ydi Gdfbd hbjd HGdYcS hHJbOe GdJNUjU Ydi ZjQg hHJSGhj GdEVeGQ hGdeLGR hGdChdi GdJhba aj UGhQI GdJYGQV EdG eY CeGQI NGQLjI Gh OGNdjI JhLH UQa GddaX Edi CeQ eYjf (B...s
(3BNQgG (B:s
... (3hgPG GdcdGe jMJed hLhOgG GdChd Cf GdMce HGdMbjbI hGdeLGR jJhba Ydi CMO GdCeQjf ef GdfU hhLhO TjA ef GdCeGQGJ GdebQQI hCfg HOhfgG dG jUM GdMce Hchf GddaX GdeSJYed MbjbI hdG eLGR Hd jLH GdJhba ajg (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3CUhd Gdabgs